PEMBERDAYAAN MASYARAKAT DALAM TANGGAP DARURAT BENCANA BANJIR MELALUI SUPPORT EDUKASI EVAKUASIDAN TRANSPORTASI PADA SARASEHAN JUMAT KLIWONAN - martono; Siti Khadijah; Dwi Ariani Sulistyowati (LPPM AN Nuur, 2025)
Background: Flooding is common in Indonesia, particularly during the rainy season, due to the country’s many rivers. About 30% of these rivers flow through densely populated areas, increasing the risk of hydrometeorological disasters, including flash floods. Floods can cause significant damage, both material and non-material, and even loss of life. Purpose: This activity aims to enhance the awareness, preparedness, and skills of residents in flood evacuation and transportation during emergencies. Method: The community service program focused on empowering members of the